A series of trials in the UK as part of the Ofcom TV white spaces pilot - Holland, Oliver (2016)
“Copyright © [2014] IEEE. Reprinted from 1st International Workshop on Cognitive Cellular Systems 2014 . ISBN: 978-1-4799-4139-1 .This material is posted here with permission of the IEEE. Internal or personal use of this material is permitted. However, permission to reprint/republish this material for advertising or promotional purposes or for creating new collective works for resale or redistribution must be obtained from the IEEE by writing to pubs-permissions@ieee.org. By choosing to view this document, you agree to all provisions of the copyright laws protecting it.”